Charles Taylor's Critique of the Modern Conceptions of Liberty and Rights and its Applications in Human Rights Education - Huang-Kun Chang (National Taipei University of Education, 2019)
The purpose of this paper is to form a more comprehensive view of rights based on Charles Taylor's critiques of the modern conceptions of liberty and rights, and to re-envision our human rights education to help our students learn an appropriate view of rights. Three main views on liberty and rights Taylor proposed are as follows. First, The ultimate goal of liberty and rights is self-realization. Therefore, the exercise of rights should be evaluated by the individual's "reflective self-evaluation" to determine how the exercise of rights corresponds with the orientation of his self-realization. Second, Rights are not inherent to human beings, but given by society. The reason the society gives people rights is based on the importance of certain human abilities. The development of such abilities is regarded as rights so that people have the possibility to demonstrate these abilities. Finally, the exercise of rights is dependent on the society. When people enjoy rights, they are relatively obligated to society. They must defend the society and maintain its development so that all members of the society could enjoy the rights. Based on the viewpoints of Taylor, this paper suggests four principles as guidelines for the implementation of human rights education. This paper also analyzes how characteristics of the "rational critical debate" conform to these principles and suggests how the activity could be used in human rights education.